Marine Biodiversity of Costa Rica: The phyla Sipuncula and Echiura - Dean, Harlan K. (2001)
Fourteen species of Sipuncula belonging to 9 genera have been reported from Costa Rican waters, mostly from the Pacific coast. Three of these species are new records for Costa Rica (Phascolion strombus (Montagu 1804), Aspidosiphon (Aspidosiphon) muelleri Diesing 1851, and Aspidosiphon (Aspidosiphon) gracilis schnehageni (W. Fisher 1946)). One species of Echiura, Thalassema steinbecki Fisher 1946, in the order Echiuroinea, has been reported from the Pacific coast of Costa Rica.